In vitro gas production and fatty acids biohydrogenation of diets containing different unsaturated fatty acids sources plus crude glycerin - Gomez-Insuasti, Arturo Samuel [UNESP]; Granja-Salcedo, Yury Tatiana [UNESP]; Vargas, Julian Andrés Castillo [UNESP]; Messana, Juliana Duarte [UNESP]; De Oliveira Sader, Ana Paula [UNESP]; Berchielli, Telma Teresinha [UNESP] (The Scientific and Technological Research Council of Turkey (TUBITAK-ULAKBIM) - DIGITAL COMMONS JOURNALS, 2021)
An in vitro trial was conducted to evaluate the effects of different unsaturated fatty acids (UFA) sources plus crude glycerin (CGL) on gas production and rumen biohydrogenation (RBH). Incubated diet corresponded to diets containing corn silage (30%) and concentrate (70%) composed of corn, urea, mineral salts, CGL, and different UFA sources as follows: no additional fat (NAF), rumen protected fat (RPF), soybean oil, linoleic acid (LA) or alpha-linolenic acid (LN). Methane concentrations in LA and LN were lower compared to NAF (p < 0.001), but when CH4 was expressed as a proportion of total gas, NAF and RPF showed the greatest values among evaluated UFA sources (p = 0.001). 18:1 t11 concentration showed a faster increase from 0 to 1 h and a slower decrease from 1 to 36 h of incubation, irrespective of UFA source. A higher C18:1 t11 production rate was observed from 1 h to 5 h of incubation, where LA and LN have higher values compared to NAF and RPF diets (p < 0.001). Diets with a high content of LA may be efficient as a nutritional approach to reduce methane production and RBH, resulting in positive effects on vaccenic acid concentrations.
Keywords: Cattle; Conjugated linoleic acid; Glycerol; Greenhouse gas; Protected fat; Soybean oil